Foot and Ankle Osteoid Osteomas. - Gurkan, Volkan; Erdogan, Ozgur (My University, 2023)
Foot and ankle osteoid osteomas (OOs) are often cancellous or subperiosteal and rarely present with a periosteal reaction. Additionally, the large number of disorders included in the differential diagnosis and the nonspecific findings on radiographs complicate the diagnosis. We performed a manual search of the senior surgeon's hospitals' operating room records for the terms "benign bone tumor," "foot," "ankle," and "osteoid osteoma" from January 2003 until December 2014. Of 87 surgically treated patients with lower extremity OOs, 9 patients (11%) with foot or ankle OOs were included. The mean age at presentation was 21 (range 6 to 30) years; all 9 (11%) patients were male. The patients were evaluated for swelling, pain, trauma history, night pain, response to pain relievers, duration of complaints, and interval to diagnosis. The mean follow-up period was 48 ± 24 months, and no recurrences had developed. The mean American Orthopaedic Foot and Ankle Society scale score was 59.04 ± 11 before surgery and 91.56 ± 6 after surgery. The difference was statistically significant at p ≤ .0003. Most previous studies have been limited to case reports. The need for findings from a case series was an essential determinant of our decision to report our results. Patients usually have been treated conservatively, often for a long period. However, delays in treatment cause social, economic, and psychological damage. In conclusion, the presence of atypical findings on radiographs has resulted in a preference for magnetic resonance imaging instead of computed tomography; however, the diffuse soft tissue edema observed on MRI can lead to the use of long-term immobilization and a delay in the diagnosis.
Keywords: ankle; foot; osteoid; osteoma; pain